2004
DOI: 10.1136/bjsm.2003.009548
|View full text |Cite
|
Sign up to set email alerts
|

Effective ways of restoring muscular imbalances of the rotator cuff muscle group: a comparative study of various training methods

Abstract: Background: Many studies have compared different training methods for improving muscular performance, but more investigations need to be directed to the restoration of muscular imbalances. Objective: To determine the most effective training for altering strength ratios in the shoulder rotator cuff. Methods: Forty eight physical education students were randomly assigned to four groups (12 per group): (a) experimental group who carried out multijoint dynamic resistance training for shoulder internal and external… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
2
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 33 publications
2
16
2
4
Order By: Relevance
“…Assim, a força dos rotadores mediais no membro dominante é maior quando comparada com o não dominante, caracterizando o mesmo desequilíbrio muscular encontrado em jogadores de voleibol (13,20) . Esportes que requerem maior simetria entre membros, como a natação, não são caracterizados por esse desequilíbrio muscular, pois esses esportes envolvem treinamento bilateral dos membros superiores, mantendo maior simetria de forças entre membros no complexo do ombro, a qual também é encontrada na população não atleta (19,21) . Além da realização de testes concêntricos, vários estudos preconizam o uso da avaliação isocinética excêntrica em atletas, devido à especificidade desse teste em relação ao gesto esportivo, pois na fase de aceleração do braço os rotadores laterais atuam de forma excêntrica (9,10,19,22) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Assim, a força dos rotadores mediais no membro dominante é maior quando comparada com o não dominante, caracterizando o mesmo desequilíbrio muscular encontrado em jogadores de voleibol (13,20) . Esportes que requerem maior simetria entre membros, como a natação, não são caracterizados por esse desequilíbrio muscular, pois esses esportes envolvem treinamento bilateral dos membros superiores, mantendo maior simetria de forças entre membros no complexo do ombro, a qual também é encontrada na população não atleta (19,21) . Além da realização de testes concêntricos, vários estudos preconizam o uso da avaliação isocinética excêntrica em atletas, devido à especificidade desse teste em relação ao gesto esportivo, pois na fase de aceleração do braço os rotadores laterais atuam de forma excêntrica (9,10,19,22) .…”
Section: Discussionunclassified
“…Esse maior volume permite aos atletas sub-21 realizarem maior número de repetição do movimento de rotação medial em relação à categoria sub-19. Além disso, segundo Malliou et al (21) exercícios gerais de membros superiores na musculação (pulley, remada, supino) produzem aumento da força nos músculos rotadores mediais e não dos laterais. Possivelmente, esse fator contribuiu para o maior desequilíbrio na categoria sub-21, uma vez que esses atletas possuem mais tempo de prática na musculação com maior intensidade.…”
Section: Discussionunclassified
“…A velocity spectrum rehabilitation protocol used to enhance a training response at various angular velocities. Ten repetitions at each angular velocity with 10-second rest between angular velocities were optimal to increase isokinetic peak torque across a velocity spectrum [23]. A total of 16 workout sessions were completed by every child in the allotted 8 weeks period.…”
Section: Procedures For Evaluationmentioning
confidence: 99%
“…The emphasis is placed on the testing and training of the internal and external rotation strength of the shoulder. Davies (1984) and Malliou et al (2004) concluded that isokinetic strengthening was the most effective method of altering the strength ratios of the RTC compared with isolated isotonic training, multi-joint dynamic resistance training, and no intervention. However, a qualitative review in 2000 (Ellenbecker and Davies) concluded that isokinetic treatment techniques were only one part of the rehabilitation process, which is tremendously diverse.…”
Section: Introductionmentioning
confidence: 99%
“…This kind of imbalance can be expressed as changes in the strength ratio (peak torque ratio) of the cuff by isokinetics (Leroux et al, 1994). In addition, isokinetic training succeeded in enhancing the strength to redress the imbalance of shoulder muscle groups and the performance of normal subjects (Malliou et al, 2004). The emphasis is placed on the testing and training of the internal and external rotation strength of the shoulder.…”
Section: Introductionmentioning
confidence: 99%